AKTIVITAS MODEL TEAM GAMES TOURNAMEN (TGT) BERBANTUAN MEDIA KOKAMI TERHADAP KETERAMPILAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS V SEKOLAH DASAR - Hafizah; Anita Imelia Sasra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the effect of the Team Games Tournament (TGT) learning model assisted by Kokami media on fifth-grade elementary students’ descriptive paragraph writing skills. A quantitative approach with a quasi-experimental pretest-posttest group design was employed. The sample consisted of 59 students, divided into an experimental group and a control group. The experimental group was taught using the TGT model supported by Kokami media, while the control group received instruction through a conventional differentiated learning method. The research instrument was a performance-based writing test assessed on content, organization, and vocabulary aspects. Data were analyzed using SPSS 23, including normality, homogeneity, and hypothesis testing via independent sample t-test. The results showed a significant increase in the average posttest scores of the experimental group compared to the control group. The significance value obtained was 0.037 (<0.05), indicating that the TGT model with Kokami media had a statistically significant positive effect. The findings suggest that combining cooperative learning strategies with interactive media can effectively enhance students’ writing abilities, foster active participation, and create a more engaging learning environment.